Makna Upacara Adat Reba (Syukuran Atas Hasil Panen) Bagi Masyarakat Bajawa Kabupaten Ngada Provinsi Nusa Tenggara Timur: Indonesia - Vercelli Elisabeth Fono; Omiano Sabu; Jeff Wilfred Mesah (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
The Meaning of the Reba Traditional Ceremony (Thanksgiving for the Harvest) for the Bajawa Community, Ngada Regency, East Nusa Tenggara Province." The results of this research show that, (1) Reba is a ceremony of thanksgiving to ancestors which is carried out in the Bajawa community, especially Bobou village. Crops will fail and people will get various kinds of diseases. In carrying out the Reba ceremony in the Bajawa community, especially Bobou village. The values ​​and meanings contained in the traditional reba ceremony in the Bajawa community, especially in Bobou village, namely a). Historical meaning (history). b) The meaning of brotherhood. A). Social value, b). Cultural values, c). The value of fortitude and hope, d). magical value, e). Peace value, f). Moral values.